STUDI DESKRIPTIF TENTANG PENATUA GEREJA MENURUT ALKITAB DAN PENGGUNAANNYA DALAM ALMANAK GKPI - Epafras Mujono; Ruth Melisa (JURNAL PENABIBLOS, 2024)
This descriptive research has several objectives: First, to explain about elders according to the Bible. Second, to explain the use of the Biblical concept of elders in the GKPI Almanac. The results of this research are: First, elders in the concept or Bible notes are in plural form, this can mean that the ministry of elders is a team ministry. Second, according to the Bible, an elder is a leadership position in a local church or congregation, one of whose duties is to shepherd the congregation. Third, the requirements for becoming a church elder according to the Bible include requirements for personal life, family life and requirements for relating to social life. Fourth, the nature and position of elders according to the GKPI Almanac are in harmony with the concepts in the Bible. Fifth, the requirements for elders according to the GKPI Almanac are in accordance with the concepts in the Bible. Sixth, the main duties of elders in the GKPI Almanac are in accordance with the Bible, but there is a little less emphasis on providing an example for congregation members. Seventh, the main duties of elders in the GKPI Almanac are described in greater or greater detail.